Thermogravimetric Analysis and Mechanical Properties of Pebble Natural Filler-Reinforced Polymer Composites Produced through a Hand Layup Technique. (20th September 2022) - Kumar, Raj; Kumar, S. Mohan; Kumar, M. E. Shashi; Kumar, V. Ravi; Kivade, Rajesh; Pavan, Jonnalagadda; Seikh, A. H.; Siddique, M.H.; Diriba, Abdi
Abstract : Using pebble and fibre in an epoxy matrix, the mechanical, dynamic, and thermal characteristics of a composite were examined. Tensile, flexural, impact, and interlaminar shear strengths are experimentally determined. In this study, we compare the mechanical performance of carbon fibre composites composed entirely of conventional epoxy (NE). The results of a comparative investigation using 15 and 20% carbon fibre in an epoxy matrix are presented. Additional categories for compressive strength and damping ratio were defined based on this performance. The epoxy resin was combined with carbon fibre (15 wt% and 20 wt%) in a unidirectional arrangement and manufactured with different fillers like pebble. The goal of this research is to better understand the bonding mechanisms between damping materials and the resin matrix in order to increase interfacial bonding performance. This information is required for both selecting the appropriate material for applications and developing a composite construction using that material.